Case report: Traumatic carotid artery dissection after 7D High-Intensity Macro- and Micro-Focused Ultrasound treatment for skin laxity of the neck - Du, Fenghe; Shao, Jiang; Lai, Zhichao; Li, Kang; Wang, Chaonan; Liu, Bao (Frontiers in Cardiovascular Medicine, 2022)
Background Trauma is a relatively uncommon etiology of carotid artery dissection. Both penetrative trauma and trivial trauma could result in carotid artery dissection. Here, we present an unusual case where carotid artery dissection was potentially triggered by the damaging heat effect of 7D High-Intensity Macro and Micro Focused Ultrasound (7D HIFU), which has been considered a safe and effective non-surgical modality for skin rejuvenation. Case summary A 41-year-old female developed a headache and clinical manifestations of cerebral infarction after 7D HIFU with the aim of removing necklines. Head and neck magnetic resonance angiography and CT angiogram showed severe stenosis and dissection of the left internal carotid artery. The patient had nothing special regarding her past history and physical examination. After left carotid artery dissection resection, autologous great saphenous vein interposition grafting, and simple mastoidectomy, the patient underwent head and neck magnetic resonance angiography, which revealed recanalization of the left internal carotid artery. Conclusion Although mild and moderate complications of 7D HIFU, including erythema, edema, transient dysesthesia, and motor nerve paresis, have been reported earlier, minimal previous literature has documented severe complications of the cosmetic procedure. However, a number of recent studies have pointed out the potential of 7D HIFU to damage adjacent, non-target tissue as a result of inappropriate focal depth of HIFU treatment. Our case is the first to indicate that 7D HIFU could lead to carotid artery dissection. By reporting the case where the damaging heat effect of 7D HIFU precipitated the carotid artery dissection HIFU, we believe that better visualization systems and more rigorous operator training are necessary to reduce the risk of the potential off-target damaging effect of 7D HIFU.